Etika dalam Paham Ekonomi Islam sebagai Suatu Pedoman dalam Berekonomi - Wahyudin Maguni (Institut Agama Islam Negeri (IAIN) Kendari, 2009)
Teaching Islam concerning economics is the part of Islam vision concerning universal ethics, this means that valid statement formula concerning base, process, and motivation, economic in society of Islami expressing ideal Moslem society has to be based on ethics proportion, because those economics of source all work, center from natural formation and with economics also tired human being was high level the than bliss and progress. Economics of Islam is a systematic effort to comprehend the problem of economics and behavior of human being related to that problem from in perspective of Islam.